2021
DOI: 10.1016/j.jbc.2021.100905
|View full text |Cite
|
Sign up to set email alerts
|

The role of PLCγ2 in immunological disorders, cancer, and neurodegeneration

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 170 publications
(211 reference statements)
0
37
0
3
Order By: Relevance
“…Also it has been approved that T2DM is connected with OA and both are having the same reason of causing their pathogenic disease , where T2DM has a pathogenic effect on OA through 2 major pathways involving oxidative stress and low-grade chronic inflammation resulting from chronic hyperglycemia and insulin resistance [7]. Pathogenic type 2 diabetes associated with progressive beta-cell impairment due to the not normal production of insulin which due to deficiency of Ser phosphorylation pathway during mTOR Ser/Thr phosphorylation pathways that will not produce normal S6K "due to deficiency in Ser and some other necessary amino acids (mainly Ser and Tyr, Leu, Pro a.a) then will lead to decreasing "or mutation" in the S6K productions, that will lead to Androgen instead of Estrogen where Estrogen characterized by presence of Ser in their molecules, that will lead to high ATPase productions with deficiency estrogen which is the main substrat for RORs pathway that later will promote the IFN gamma, IFN-beta, and alpha that can lead to increasing in "catabolic effects" with decreasing in the ROR pathways "anabolic process" and decreasing in proper PLCγ2 productions that reflect Ca+ precipitations and arterial hypertension.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Also it has been approved that T2DM is connected with OA and both are having the same reason of causing their pathogenic disease , where T2DM has a pathogenic effect on OA through 2 major pathways involving oxidative stress and low-grade chronic inflammation resulting from chronic hyperglycemia and insulin resistance [7]. Pathogenic type 2 diabetes associated with progressive beta-cell impairment due to the not normal production of insulin which due to deficiency of Ser phosphorylation pathway during mTOR Ser/Thr phosphorylation pathways that will not produce normal S6K "due to deficiency in Ser and some other necessary amino acids (mainly Ser and Tyr, Leu, Pro a.a) then will lead to decreasing "or mutation" in the S6K productions, that will lead to Androgen instead of Estrogen where Estrogen characterized by presence of Ser in their molecules, that will lead to high ATPase productions with deficiency estrogen which is the main substrat for RORs pathway that later will promote the IFN gamma, IFN-beta, and alpha that can lead to increasing in "catabolic effects" with decreasing in the ROR pathways "anabolic process" and decreasing in proper PLCγ2 productions that reflect Ca+ precipitations and arterial hypertension.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…As the GTPase is a regulator tool for BH4 and NO 3 productions for synthase repair and activity, As, S6K1 is the main regulator for PLCγ1 synthesis and then for PLCγ2 synthesis upon synthase functions which later will migrate for beta-cells maturation and survival upon productions of firstly CXCL12 then CXCR4 productions . Also, it has been approved that T2DM is connected with OA and both are having the same reason of causing their pathogenic disease, where T2DM has a pathogenic effect on OA through 2 major pathways involving oxidative stress and low-grade chronic inflammation resulting from chronic hyperglycemia and insulin resistance [7]. Pathogenic type 2 diabetes associated with progressive beta-cell impairment due to the not normal production of insulin which due to deficiency of Ser phosphorylation pathway during mTOR Ser/Thr phosphorylation pathways that will not produce normal S6K "due to deficiency in Ser and some other necessary amino acids (mainly Ser, Tyr, Leu, Pro a.a.) then will lead to decreasing "or mutation" in the S6K productions, that will lead to Androgen production instead of Estrogen where Estrogen characterized by presence of Ser in their molecules "and is the substrates for ROR anabolic signaling pathways", that will lead to high ATPase productions (due to availability of purines with decreasing in pyrimidine synthesis) with deficiency estrogen synthesis that later will promote the IFN gamma, IFN-beta, and alpha that can lead to increasing in "catabolic processes " with decreasing in the ROR pathways "anabolic process" and decreasing in proper PLCγ2 productions that will reflect Ca+ precipitations and arterial hypertension.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…KEGG analysis revealed that the FcεRI pathway was enriched in downregulated genes including PLCG2, ALOX5AP and INPP5D. In particular, PLCG2, one of the gene in our signature, is a critical signaling molecule in both the innate and adaptive immune systems [ 47 ], being activated in monocytes, macrophages, and mast cells through crosslinking of the FcεR and FcγR [ 48 ]. Since macrophages actually represent the major FcεR-expressing effector cells, we could speculate that PLCG2 deficiency, by impairing the FcεR signaling in macrophages, will finally reduce the proinflammatory and anti-tumoral states induced by IgE, with a strong impact on response to therapy.…”
Section: Discussionmentioning
confidence: 99%